ABOUT THE NAMES OF PUBLIC CATERING ESTABLISHMENTS IN THE CITY OF KARSHI (American Journal of Research in Humanities and Social Sciences, 2023)
The article is devoted to the analysis of the names of catering establishments in the city of Karshi. In the Uzbek language, it is recommended to use the term "canteen" as an alternative term to "General dining establishment". In the article, the relation of the names of the restaurants to their own and adopted layers, the role of the onomastic and appellative lexicon in the motive of their appearance, etc. have been studied. In addition, the importance of differentiating the analyzed onomastic units according to their statistical, genetic and semantic characteristics is revealed on the basis of clear evidence.